2016
DOI: 10.1017/s136898001500378x
|View full text |Cite
|
Sign up to set email alerts
|

Public health nutrition capacity: assuring the quality of workforce preparation for scaling up nutrition programmes

Abstract: Objective: To describe why and how capacity-building systems for scaling up nutrition programmes should be constructed in low-and middle-income countries (LMIC). Design: Position paper with task force recommendations based on literature review and joint experience of global nutrition programmes, public health nutrition (PHN) workforce size, organization, and pre-service and in-service training. Setting: The review is global but the recommendations are made for LMIC scaling up multisectoral nutrition programmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
2
41
0
4
Order By: Relevance
“…These socio-demographic factors may be related to food intake, as higher education attainment is associated with better food knowledge and better income, enabling improved accessibility to a variety of foods. 15,16 These findings are also in line with the National and United rankings of Lesotho and considered to be major challenges that contribute to food insecurity. 17 Of concern is the high prevalence of obesity in both rural and especially urban participants included in this study.…”
Section: Resultssupporting
confidence: 67%
“…These socio-demographic factors may be related to food intake, as higher education attainment is associated with better food knowledge and better income, enabling improved accessibility to a variety of foods. 15,16 These findings are also in line with the National and United rankings of Lesotho and considered to be major challenges that contribute to food insecurity. 17 Of concern is the high prevalence of obesity in both rural and especially urban participants included in this study.…”
Section: Resultssupporting
confidence: 67%
“…The poor performance of the final year students in general in the present study can perhaps be attributed to the little emphasis or priority given to nutrition education during the training of midwives (Arish et al, 2016;Sodjinou et al, 2014). Other factors include the level of nutritional competences exhibited by tutors (Sethuraman et al, 2015) and issues related to the lack of essential aspects of human nutrition in courses taught (Shrimpton et al, 2016). In this study, majority (94.3%) of the final year students indicated that they studied only one nutrition course throughout the entire three year duration of the training programme.…”
Section: Discussionmentioning
confidence: 62%
“…Low-and middle-income countries deserve greater attention [52,53] because their nutrition-related workforce needs to tackle maternal and child undernutrition, which are the objectives to sustainable development [52].…”
Section: Checklist For Qualitative Researchmentioning
confidence: 99%